Electronic device using self-healing biodegradable elastic conductor and method for manufacturing the same

KR103015596B1Active Publication Date: 2026-09-04KOREA UNIV RES & BUSINESS FOUND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240161437
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2026-09-04
Estimated Expiration
2044-11-13

Smart Images

  • Figure 112024125073345-PAT00001_ABST
    Figure 112024125073345-PAT00001_ABST
Patent Text Reader

Abstract

An electronic device using a self-healing biodegradable elastic conductor and a method for manufacturing the same are disclosed. A method for manufacturing an electronic device using a self-healing biodegradable elastic conductor comprises the steps of: preparing a base film; spin-coating a conductive polymer solution onto the base film to form an electrode pattern; and annealing the electrode pattern, wherein the base film is made of a polymer in which a diisocyanate is bonded to both ends of the biodegradable polymer and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate, and the conductive polymer solution is a mixed solution of a conductive polymer, an ionic liquid, polyethylene glycol, and glycerol.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electronic device using a self-healing biodegradable elastic conductor and a method for manufacturing the same. More specifically, the invention relates to an electronic device using a self-healing biodegradable elastic conductor that functions stably when inserted into a living organism and has a recovery function against physical and / or electrical damage, and a method for manufacturing the same. Background Technology

[0002] Transient electronics is a technology in which a device stably performs its inherent function for a certain period of time and then dissolves, decomposes, or separates within the body or environment, thereby eliminating its physical state and electrical function; this has brought innovation to the fields of biomedical and eco-friendly electronic systems.

[0003] Time-sensitive electronic devices are generally applied to the skin and body organs in attachable or implantable forms; flexibility and elasticity are essential to minimize damage to biological tissues during application and to ensure the device operates stably even under frequent movement and deformation of the tissues.

[0004] Meanwhile, since implanted devices cannot or are difficult to repair if they fail, ensuring stable long-term operation is a critical technical challenge. While self-healing materials are being introduced to address this issue, limitations still exist in terms of biodegradability, mechanical properties, durability, and processability.

[0005] Furthermore, to realize a self-healing bio-implantable electronic device capable of reliably performing advanced functions, both the polymer material serving as the substrate and protective layer for the electronic component and the conductive layer material required for the device's components and electrical connections must possess self-healing capabilities; additionally, elemental technologies are required to realize strong bonding characteristics between the two materials for stable operation.

[0006] Accordingly, research is required to resolve the aforementioned problems. The problem to be solved

[0007] The present invention provides a method for manufacturing an electronic device using a self-healing biodegradable elastic conductor having biodegradability, elasticity, and conductivity.

[0008] In addition, the present invention provides an electronic device using a self-healing biodegradable elastic conductor having a self-healing function in the event of physical or electrical damage.

[0009] In addition, the present invention provides an electronic device using a self-healing biodegradable elastic conductor that can be inserted into and / or implanted in vivo.

[0010] In addition, the present invention provides an electronic device using a self-healing biodegradable elastic conductor with excellent bonding strength between a base film and an electrode pattern. means of solving the problem

[0011] An electronic device using a self-healing biodegradable elastic conductor according to the present invention and a method for manufacturing the same comprises the steps of: preparing a base film; spin-coating a conductive polymer solution onto the base film to form an electrode pattern; and drying the electrode pattern, wherein the base film is made of a polymer in which a diisocyanate is bonded to both ends of the biodegradable polymer and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate, and the conductive polymer solution may be a mixed solution of a conductive polymer, an ionic liquid, polyethylene glycol, and glycerol.

[0012] In addition, the biodegradable polymer may be PLCL (poly(L-lactide-co-ε-caprolactone)), the diisocyanate may be IPDI (isophorone diisocyanate (IPDI)), and the chain extender may be AFD (Bis(4-aminophenyl)disulfide molecule).

[0013] In addition, the conductive polymer is selected from at least one of PEDOT:PSS, polypyrrole (PPy), and polyaniline (PANI), and the ionic liquid may be P14[TFSI](N-methyl-N-butylpyrrolidiniumbis(trifluoromethanesulfonyl)imide).

[0014] In addition, the conductive polymer, the ionic liquid, the polyethylene glycol, and the glycerol may be mixed in a ratio of 1:2:4:5.

[0015] In addition, the annealing step may heat-treat the base film and the electrode pattern in a temperature range of 130 to 150 ℃.

[0016] In addition, the base film may have a thickness of 10 to 500 μm, and the electrode pattern may have a thickness of 0.1 μm to 5 μm.

[0017] An electronic device using a self-healing biodegradable elastic conductor according to the present invention comprises a first base film; and a first electrode pattern adhered to the upper surface of the first base film, wherein the first base film is made of a polymer in which a diisocyanate is bonded to both ends of the biodegradable polymer and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate, and the first electrode pattern can be formed by spin-coating a conductive polymer solution mixed with a conductive polymer, an ionic liquid, polyethylene glycol, and glycerol onto the upper surface of the first base film.

[0018] Additionally, the apparatus further comprises a second base film provided on the upper surface of the first electrode pattern; and a second electrode pattern adhered to the upper surface of the second base film, wherein the second base film is made of a polymer in which a diisocyanate is bonded to both ends of a biodegradable polymer and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate, and the second electrode pattern can be formed by spin-coating a conductive polymer solution mixed with a conductive polymer, an ionic liquid, polyethylene glycol, and glycerol onto the upper surface of the second base film.

[0019] Additionally, the biodegradable polymer is PLCL (poly(L-lactide-co-ε-caprolactone)), the diisocyanate is IPDI (isophorone diisocyanate (IPDI)), the chain extender is AFD (Bis(4-aminophenyl)disulfide molecule), the conductive polymer is selected from at least one of PEDOT:PSS, polypyrrole (PPy) and polyaniline (PANI), and the ionic liquid may be P14[TFSI] (N-methyl-N-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide).

[0020] In addition, the first base film may have a thickness of 10 to 500 μm, and the first electrode pattern may have a thickness of 0.1 μm to 5 μm. Effects of the invention

[0021] According to the present invention, a self-healing electronic device capable of being inserted into and / or implanted in vivo can be manufactured by bonding a first base film having a first electrode pattern and a second base film having a second electrode pattern.

[0022] In addition, according to the present invention, the first base film having a first electrode pattern and the second base film having a second electrode pattern can self-heal when damaged, so the stability of physical / electrical performance can be improved.

[0023] In addition, according to the present invention, the temperature, humidity, and pressure within the body can be monitored through the first electrode pattern and the second electrode pattern.

[0024] In addition, according to the present invention, high adhesion can be achieved through physical and chemical bonding between the base film and the electrode pattern. Brief explanation of the drawing

[0025] FIG. 1 is a diagram showing the structure of an electronic device using a self-healing biodegradable elastic conductor according to an embodiment of the present invention. Figure 2 is a diagram showing the manufacturing process of the first base film of Figure 1. FIG. 3 is a flowchart illustrating the manufacturing process of an electronic device using a self-healing biodegradable elastic conductor according to an embodiment of the present invention. Figure 4 is a photograph showing the process of testing the self-healing ability of the first base film according to an embodiment of the present invention. Figure 5 is a graph showing the stress-strain ratio according to the recovery time of the first base film of Figure 4. FIG. 6 is a photograph showing a first electrode pattern according to an embodiment of the present invention. Figure 7 is an SEM image showing the change in the area where the first electrode pattern of Figure 6 was cut. Figure 8 is a graph showing the electrical conductivity and recovery time of electrode patterns measured by varying the polyethylene glycol (PEG) ratio. Figure 9 is a graph showing the electrical conductivity and elasticity of the electrode pattern measured by varying the P14[TFSI] ratio. FIG. 10 is a graph measuring the change in current when repeated damage occurs to the first electrode pattern according to an embodiment of the present invention. FIG. 11 is a drawing showing the results of a wrap shear test of an electronic device according to a comparative example and an embodiment of the present invention. FIG. 12 is a diagram showing the physical coupling of a first base film and a first electrode pattern according to an embodiment of the present invention. FIG. 13 is a diagram showing the molecular structure of a first base film and a first electrode pattern according to an embodiment of the present invention. FIG. 14 is a diagram showing the results of a self-healing ability test of a specimen prepared according to an embodiment of the present invention. FIG. 15 is a diagram showing the results of testing the physical and electrical stability of an electric device using a self-healing biodegradable elastic conductor according to an embodiment and a comparative example of the present invention under aqueous conditions. FIG. 16 is a drawing showing an electrical device using a self-healing biodegradable elastic conductor according to an embodiment of the present invention. FIG. 17 is a diagram showing an electrical device using a self-healing biodegradable elastic conductor according to an embodiment of the present invention applied in a living body. Figure 18 is a graph showing the results of the recovery of function from artificial damage to the electrical device while monitoring the urination behavior of the bladder in real time through the electrical device using the self-healing biodegradable elastic conductor of Figure 17. Specific details for implementing the invention

[0026] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. However, the technical concept of the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art.

[0027] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Additionally, in the drawings, the thicknesses of the films and regions are exaggerated for the effective description of the technical content.

[0028] Additionally, although terms such as first, second, third, etc., have been used to describe various components in the various embodiments of this specification, these components should not be limited by such terms. These terms are used merely to distinguish one component from another. Accordingly, what is referred to as the first component in one embodiment may be referred to as the second component in another embodiment. Each embodiment described and illustrated herein also includes its complementary embodiment. Furthermore, in this specification, "and / or" is used to mean including at least one of the components listed before and after it.

[0029] In the specification, singular expressions include plural expressions unless the context clearly indicates otherwise. Furthermore, terms such as "include" or "have" are intended to specify the existence of the features, numbers, steps, components, or combinations thereof described in the specification, and should not be understood as excluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof. Additionally, in this specification, "connection" is used to include both indirectly connecting multiple components and directly connecting them.

[0030] In addition, in describing the present invention below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0032] FIG. 1 is a diagram showing the structure of an electronic device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention.

[0033] Referring to FIG. 1, an electronic device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention has a stacked structure in a direction perpendicular to the ground and is provided to be capable of self-healing from physical / electrical damage. The electronic device (10) using a self-healing biodegradable elastic conductor includes a first base film (100), a first electrode pattern (200), a second base film (300), and a second electrode pattern (400).

[0034] The first base film (100) is a bottom layer having a predetermined area and thin thickness. The first base film (100) can be manufactured as a self-healing biodegradable elastic conductor. The first base film (100) can be provided as a polymer having a structure in which a diisocyanate is bonded to both ends of a biodegradable elastic polymer, and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate. According to an example, the first base film (100) can be provided as a polymer having a structure in which IPDI (isophorone diisocyanate (IPDI)) is bonded to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)), and AFD (Bis(4-aminophenyl)disulfide molecule), a chain extender, is bonded to both ends of IPDI. According to an example, the PLCL can be provided with a molecular weight in the range of 500 to 5000.

[0035] The first base film (100) may have a thickness of 10 to 500 μm. Preferably, it has a thickness of 100 μm. The first base film (100) is biodegradable and elastic.

[0036] The first electrode pattern (200) is made of a self-healing, biodegradable, elastic, and conductive polymer and is formed on the upper surface of the first base film (100). The first electrode pattern (200) can be manufactured by spin-coating a conductive polymer solution onto the upper surface of the first base film (100), and then drying and heat-treating it. According to an embodiment, the conductive polymer solution is prepared by mixing a conductive polymer, an ionic liquid, polyethyleneglycol (PEG), and glycerol.

[0037] The first electrode pattern (200) has a predetermined arrangement and is formed with a thin thickness. According to an embodiment, the first electrode pattern (200) may have a thickness of 0.1 μm to 5 μm. Preferably, it has a thickness of 2 μm. The first electrode pattern (200) is biodegradable, elastic, and conductive.

[0038] The second base film (300) is laminated on the upper surface of the first electrode pattern (200) and the first base film (100).

[0039] The second base film (300) can be manufactured as a self-healing biodegradable elastic conductor. The second base film (300) can be provided as a polymer having a structure in which a diisocyanate is bonded to both ends of a biodegradable elastic polymer, and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate. According to an example, the second base film (300) can be provided as a polymer having a structure in which IPDI (isophorone diisocyanate (IPDI)) is bonded to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)), and AFD (Bis(4-aminophenyl)disulfide molecule), a chain extender, is bonded to both ends of IPDI. According to an example, the PLCL can be provided with a molecular weight in the range of 500 to 5000.

[0040] The second base film (300) may have a thickness of 10 to 500 μm. Preferably, it has a thickness of 100 μm. The second base film (300) is biodegradable and elastic. According to an example, the second base film (300) is made of the same material as the first base film (100).

[0041] The second electrode pattern (400) is made of a self-healing, biodegradable, elastic, and conductive polymer and is formed on the upper surface of the second base film (300). The second electrode pattern (300) can be manufactured by spin-coating a conductive polymer solution onto the upper surface of the second base film (300), and then drying and heat-treating it. According to an embodiment, the conductive polymer solution is prepared by mixing a conductive polymer, an ionic liquid, polyethyleneglycol (PEG), and glycerol.

[0042] The second electrode pattern (400) has a predetermined arrangement and is formed with a thin thickness. According to an embodiment, the second electrode pattern (400) may have a thickness of 0.1 μm to 5 μm. Preferably, it has a thickness of 2 μm. The second electrode pattern (400) is biodegradable, elastic, and conductive. According to an embodiment, the second electrode pattern (400) is formed from the same material as the first electrode pattern (100).

[0044] FIG. 2 is a diagram showing the manufacturing process of the first base film (100) of FIG. 1, and FIG. 3 is a flowchart showing the manufacturing process of an electronic device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention.

[0045] Referring to FIGS. 2 and 3, the manufacturing process of a self-healing electronic device (10) according to an embodiment of the present invention includes a first base film preparation step (S10), a first electrode pattern formation step (S20), a first annealing step (S30), a second base film preparation step (S40), a second electrode pattern formation step (S50), a second annealing step (S60), and a third annealing step (S70).

[0046] The first base film preparation step (S10) prepares a first base film (100) on a glass substrate molded with PDMS.

[0047] The first base film (100) can be manufactured from a polymer in which a diisocyanate is bonded to both ends of a biodegradable elastic polymer, and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate.

[0048] According to an embodiment, the first base film (SH-PLCL) (100) can be manufactured by attaching IPDI (isophorone diisocyanate (IPDI)) to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)) and then attaching AFD (Bis(4-aminophenyl)disulfide molecule), a chain extender, to both ends of IPDI. The first base film (SH-PLCL) (100) has elasticity, strength, and durability through a structure in which IPDI and AFD are attached as hard segments to both ends of PLCL, which is a soft segment.

[0049] The first base film (SH-PLCL) (100) can be manufactured with a predetermined area and thin thickness. According to an example, the first base film (SH-PLCL) (100) can be manufactured with a thickness of 10 to 500 μm. Preferably, it is manufactured with a thickness of 100 μm.

[0050] The first electrode pattern formation step (S20) forms a first electrode pattern (200) by spin-coating a conductive polymer solution onto the upper surface of the first base film (100). The conductive polymer solution is prepared by mixing a conductive polymer, an ionic liquid, polyethyleneglycol (PEG), and glycerol. According to an example, the conductive polymer may be selected from at least one of PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), polypyrrole (PPy), and polyaniline (PANI), and the ionic liquid is P14[TFSI] (N-methyl-N-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide). Preferably, the conductive polymer solution may be a mixture of PEDOT:PSS, P14[TFSI], polyethyleneglycol, and glycerol in a ratio of 1:2:4:5.

[0051] In the first electrode pattern formation step (S20), a pattern is formed on the upper surface of the first base film (100) using the conductive polymer solution through a PDMS stencil mask, and then dried on a hot plate at 50°C for 10 minutes.

[0052] The first electrode pattern (200) has a predetermined arrangement and can be formed with a thin thickness. According to an embodiment, the first electrode pattern (200) can be formed with a thickness of 0.1 μm to 5 μm. Preferably, it is formed with a thickness of 2 μm. The first electrode pattern (200) is provided as a pressure sensor as a lower electrode of an electronic device.

[0053] The first annealing step (S30) involves removing the PDMS stencil mask from the first base film (100) on which the first electrode pattern (200) is formed, and then performing an annealing process at a temperature of 140°C for 1 hour. During this process, the contact area between the first electrode pattern (200) and the first base film (100) is completely dried and then strongly adhered.

[0054] The second base film preparation step (S40) prepares a second base film (300) on a glass substrate cast with PDMS. The second base film (300) can be manufactured from a polymer in which a diisocyanate is bonded to both ends of a biodegradable elastic polymer, and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate. According to an example, the second base film (200) can be manufactured by bonding IPDI (isophorone diisocyanate (IPDI)) to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)) and then bonding AFD (Bis(4-aminophenyl)disulfide molecule), a chain extender, to both ends of IPDI. The second base film (300) has elasticity, strength, and durability through a structure in which IPDI and AFD are bonded as hard segments to both ends of PLCL, which is a soft segment.

[0055] The second base film (300) can be manufactured with a predetermined area and thin thickness. According to an example, the second base film (300) can be manufactured with a thickness of 10 to 500 μm. Preferably, it is manufactured with a thickness of 100 μm.

[0056] The second electrode pattern formation step (S50) forms a second electrode pattern (400) by spin-coating a conductive polymer solution onto the upper surface of the second base film. The conductive polymer solution is prepared by mixing a conductive polymer, an ionic liquid, polyethyleneglycol (PEG), and glycerol. According to an example, the conductive polymer may be selected from at least one of PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), polypyrrole (PPy), and polyaniline (PANI), and the ionic liquid is P14[TFSI] (N-methyl-N-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide). Preferably, the conductive polymer solution may be a mixture of PEDOT:PSS, P14[TFSI], polyethyleneglycol, and glycerol in a ratio of 1:2:4:5.

[0057] In the second electrode pattern formation step (S50), a second electrode pattern (400) of a predetermined shape is formed using the conductive polymer solution with a PDMS stencil mask, and then dried on a hot plate at 50°C for 10 minutes.

[0058] The second electrode pattern (400) has a predetermined arrangement and can be formed with a thin thickness. According to an embodiment, the second electrode pattern (400) can be formed with a thickness of 0.1 μm to 5 μm. Preferably, it is formed with a thickness of 2 μm. The second electrode pattern (400) is provided as an upper electrode of an electronic device, and is used as a humidity sensor, a temperature sensor, and a capacitive pressure sensor.

[0059] In the second annealing step (S60), after removing the PDMS stencil mask from the second base film (300) on which the second electrode pattern (400) is formed, an annealing process is performed at 140°C for 1 hour. During this process, the contact area between the second electrode pattern (400) and the second base film (300) is completely dried and then strongly adhered.

[0060] The third annealing step (S70) assembles the first base film (100) on which the first electrode pattern (200) is formed and the second base film (300) on which the second electrode pattern (400) is formed. The bottom surface of the second base film (300) on which the second electrode pattern (400) is formed is aligned with the upper surface of the first base film (100) on which the first electrode pattern (200) is formed, and an annealing process is performed by applying a temperature of 80°C and a pressure of approximately 100 kPa for 3 hours. During this process, the first base film (100) on which the first electrode pattern (200) is formed and the second base film (300) on which the second electrode pattern (400) is formed are bonded in a laminated structure.

[0061] A protective film is formed on the first base film (100) and the second base film (300) after adhesion is completed using a transfer printing process.

[0062] An electronic device using the self-healing biodegradable elastic conductor described above can transmit electrical signals detected from the sensors to the outside by connecting a flexible anisotropic conductive film (ACF) cable.

[0064] FIG. 4 is a photograph showing the process of testing the self-healing ability of a first base film (100) according to an embodiment of the present invention. FIG. 4 (a) shows the first base film (100) after being cut and joined, FIG. 4 (b) shows the first base film (100) after being stretched and joined, and FIG. 4 (c) shows the first base film (100) after being stretched and then having bending (left) and twisting (right) operations performed.

[0065] Referring to FIG. 4, a first base film (100) according to an embodiment of the present invention was cut and physically bonded at room temperature (RT), and then stretched by about 500% in the longitudinal direction. Then, after 1 minute had elapsed since the stretched first base film (100) recovered, bending and twisting operations were performed on the bonded portion. It was confirmed that, in the state where the first base film (100) was bonded after physical cutting, no separation or / or deformation of the bonded portion occurred even with bending and twisting operations.

[0067] FIG. 5 is a graph showing the stress-strain rate according to the recovery time of the first base film (SH-PLCL) (100) of FIG. 4.

[0068] Referring to FIG. 5, the first base film (SH-PLCL) (100) according to an embodiment of the present invention showed that the recovery efficiency increased to 80% within 3 hours at room temperature and reached about 100% after 12 hours. Through this, it can be seen that even if physical cutting and deformation are applied to the first base film (SH-PLCL) (100), the mechanical properties are fully recovered after about 12 hours at room temperature.

[0070] FIG. 6 is a photograph showing a first electrode pattern (200) according to an embodiment of the present invention, and FIG. 7 is an SEM image showing a change in the cut area of ​​the first electrode pattern (200) of FIG. 6. FIG. 7 (a) and (b) show a change in the cut area.

[0071] Referring to FIGS. 6 and FIGS. 7, the first electrode pattern (200) according to an embodiment of the present invention has flexibility, and when physically cut, the boundary of the cut area can be self-bonded.

[0073] Figure 8 is a graph showing the electrical conductivity and recovery time of electrode patterns (200, 400) with different polyethylene glycol (PEG) ratios.

[0074] Electrode patterns were formed with a ratio of PEDOT:PSS:P14[TFSI]:glycerol of 1:2:5 and a PEG content as shown in [Table 1]. After cutting each of the electrode patterns, the electrical conductivity was measured and the recovery time was observed.

[0075] division PEDOT:PSS P14[TFSI] Glycerol PEG 1 1 2 5 0 2 1 2 5 1 3 1 2 5 2 4 1 2 5 4 5 1 2 5 8

[0077] Referring to Fig. 8, it can be seen that when PEG is not included, the electrical conductivity is measured to be less than 20 S / cm, and self-healing does not occur after cutting.

[0078] When the PEG ratio is 1, the electrical conductivity is measured to be less than 300 S / cm, and it was found that recovery after cutting takes about 100 seconds or more.

[0079] When the ratio of PEG is 2, the electrical conductivity is measured to be 400 S / cm or higher, and it was found that recovery after cutting takes about 10 seconds or more.

[0080] When the PEG ratio is 8, the electrical conductivity is measured to be approximately 350 S / cm, and it was found that recovery after cutting takes less than 5 seconds.

[0081] According to an embodiment of the present invention, when the ratio of PEG is 4, the electrical conductivity is measured to be about 400 S / cm, and recovery after cutting takes less than about 5 seconds, so it can be seen that it has high electrical conductivity and a fast recovery time.

[0083] Figure 9 is a graph showing the electrical conductivity and elasticity of electrode patterns (200, 400) measured by varying the P14[TFSI] ratio.

[0084] After forming an electrode pattern with a ratio of PEDOT:PSS : polyethylene glycol (PEG) : glycerol of 1:4:5 and the content of P14[TFSI] as shown in [Table 2], electrical conductivity and elasticity were measured.

[0085] division PEDOT:PSS PEG Glycerol P14[TFSI] 1 1 4 5 0 2 1 4 5 1 3 1 4 5 2 4 1 4 5 3 5 1 4 5 4

[0087] Referring to Figure 9, it was found that when P14[TFSI] is not included, it has an electrical conductivity of less than 600 S / cm and can be stretched up to about 10%.

[0088] When the ratio of P14[TFSI] is 1, it has an electrical conductivity of 450 S / cm and is found to be stretchable up to about 40%.

[0089] When the ratio of P14[TFSI] is 3, it has an electrical conductivity of 300 S / cm and is found to be stretchable up to about 70%.

[0090] When the ratio of P14[TFSI] is 4, it has an electrical conductivity of less than 300 S / cm and is found to be stretchable up to about 75%.

[0091] According to an embodiment of the present invention, when the ratio of P14[TFSI] is 2, it is shown to have an electrical conductivity of less than 450 S / cm and be stretchable up to about 70%, indicating high electrical conductivity and elasticity.

[0093] FIG. 10 is a graph measuring the change in current when repeated damage occurs to the first electrode pattern (200) according to an embodiment of the present invention. For measurement, a force of 2N was applied to the first electrode pattern (200) using a cross-sectional knife, and as a result, damage occurred to the first electrode pattern (200) multiple times.

[0094] Referring to FIG. 10, it is confirmed that when repeated damage occurs to the first electrode pattern (200), the current decreases each time damage occurs, but the current increases again within a short time and recovers to the level before the damage. Even if the electrical conductivity of the first electrode pattern (200) decreases due to damage caused by an external force, it can recover the electrical conductivity before the damage within a few seconds.

[0096] FIG. 11 is a diagram showing the lab shear test results of an electronic device (10) using a self-healing biodegradable elastic conductor according to a comparative example and an embodiment of the present invention.

[0097] In the first comparative example (a), glass was used as the first base film (100) and the second base film, and an electrode pattern was formed between the first base film and the second base film using the conductive polymer solution, and then an annealing treatment was performed to produce a specimen in which an electrode pattern was provided between the upper and lower glass.

[0098] In the second comparative example (b), PDMS was used as the first base film and the second base film, and an electrode pattern was formed between the first base film and the second base film using the conductive polymer solution, and an annealing treatment was performed to produce a specimen in which an electrode pattern is provided between the upper and lower PDMS.

[0099] In the third comparative example (c), PI (Polyimide) was used as the first base film and the second base film, and an electrode pattern was formed between the first base film and the second base film using the conductive polymer solution, and an annealing treatment was performed to produce a specimen in which an electrode pattern is provided between the upper and lower PI.

[0100] In Comparative Example 4 (d), PLCL (poly(L-lactide-co-ε-caprolactone)) was used as the first base film and the second base film, and an electrode pattern was formed between the first base film and the second base film using the conductive polymer solution to produce a specimen in which an electrode pattern is provided between the upper and lower PLCLs.

[0101] In embodiment (e) of the present invention, a first base film (SH-PLCL) and a second base film (SH-PLCL) were prepared using a polymer in which IPDI (isophorone diisocyanate (IPDI)) was attached to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)), and a chain extender AFD (Bis(4-aminophenyl)disulfide molecule) was attached to both ends of IPDI. An electrode pattern (SH-CC) was formed between the first base film (SH-PLCL) and the second base film (SH-PLCL) using the conductive polymer solution, and an annealing treatment was performed to prepare a specimen in which an electrode pattern is provided between the first base film (SH-PLCL) and the second base film (SH-PLCL).

[0102] The shear strength was measured by extending both ends of the above specimens (a~e) outward (F).

[0103] Referring to FIG. 11, specimens (a, b) according to the first and second comparative examples were measured to have an adhesive strength (Lap-shear force (kPa)) close to 0, specimen (c) according to the third comparative example was measured to have an adhesive strength of about 25 kPa, and specimen (d) according to the fourth comparative example was measured to have an adhesive strength of about 50 kPa.

[0104] On the other hand, the specimen (e) according to the embodiment of the present invention exhibits high shear strength with an adhesive strength of approximately 160 kPa, and it can be confirmed that a strong bond is formed between the first base film (SH-PLCL), the electrode pattern (SH-CC), and the second base film (SH-PLCL).

[0106] FIG. 12 is a diagram showing the physical bonding of a first base film (SH-PLCL) (100) and a first electrode pattern (SH-CC) (200) according to an embodiment of the present invention. FIG. 12 (a) shows an image showing the bonding between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200), FIG. 12 (b) shows an SEM image of the interface between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200), and FIG. 12 (c) shows the elemental analysis results of the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200).

[0107] Referring to FIG. 12, the interface between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200) is physically bonded by the interpenetration of polymer chains. In the SEM image of the interface between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200), an area that appears indistinct and diffused is observed at the interface between the first electrode pattern (SH-CC) (200) and the first base film (SH-PLCL) (100), which is formed with a thickness of 5 μm. As a result of elemental analysis of the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200), a large amount of fluorine element, which is present only in the first electrode pattern (SH-CC) (200), is confirmed at the interface between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200). This indicates that a physical bond has been formed between the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200) due to mutual penetration.

[0109] FIG. 13 is a diagram showing the molecular structure of a first base film (SH-PLCL) (100) and a first electrode pattern (SH-CC) (200) according to an embodiment of the present invention.

[0110] Referring to FIG. 13, the first base film (SH-PLCL) (100) has a plurality of hydrogen bonding sites, and the first electrode pattern (SH-CC) (200) also has hydrogen bonding sites including polyethylene glycol (PEG) and glycerol. When the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200) are bonded, a plurality of hydrogen bonds are formed through the hydrogen bonding sites at their interface, and chemical bonding is achieved.

[0112] As described above, the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200) can form a strong bond due to physical bonding caused by mutual penetration of polymer chains at the bonding surface of the first base film (SH-PLCL) (100) and the first electrode pattern (SH-CC) (200) and chemical bonding caused by hydrogen bonding at hydrogen bonding sites.

[0114] FIG. 14 is a diagram showing the results of a self-healing ability test of a specimen prepared according to an embodiment of the present invention. FIG. 14 (a) is an image showing the change in the cut area of ​​the specimen, FIG. 14 (b) is a graph measuring the change in current when repeated damage occurs to the specimen, and FIG. 14 (c) is the tensile strain-conductivity of the specimen recovered after cut.

[0115] Referring to (a), a specimen was fabricated by connecting a self-healing biodegradable elastic conductor, made of a first base film (SH-PLCL) (100) and a first electrode pattern (SH-CC) (200) according to an embodiment of the present invention, to an LED (light-emitting diode) to provide an electrical connection to the LED, and then the specimen was cut and the changes were observed. Although the current supplied to the LED decreased due to the cutting of the specimen, the cut surface of the specimen self-bonded for 1 minute and recovered the electrical characteristics prior to the cutting.

[0116] Referring to (b), the specimen was repeatedly healed for repeated cutting and recovered its previous level of conductivity within about 2 minutes.

[0117] Referring to (c), it was confirmed that the specimen can be stretched up to 500% in a cut and self-healed state. Additionally, it was found that when the self-healed specimen after cutting is stretched, the electrical conductivity gradually decreases and maintains about 10% of the initial conductivity.

[0119] FIG. 15 is a diagram showing the results of testing the physical and electrical stability of an electric device using a self-healing biodegradable elastic conductor according to an embodiment and a comparative example of the present invention under aqueous conditions. (a) is an image showing the change in the electrode pattern after immersing the electric device according to an embodiment and a comparative example of the present invention in a phosphate buffered saline solution and ultrasonically treating it, (b) is the impedance measurement result of the electric device according to an embodiment and a comparative example of the present invention after ultrasonically treating it, and (c) is the cyclic voltage-current curve of the electric device according to an embodiment and a comparative example of the present invention after ultrasonically treating it.

[0120] The specimen (PLCL) according to the comparative example was fabricated by manufacturing a base film with PLCL and forming an electrode pattern on the upper surface of the PLCL using the conductive solution.

[0121] A specimen (SH-PLCL) according to an embodiment of the present invention was fabricated by attaching IPDI (isophorone diisocyanate (IPDI)) to both ends of PLCL (poly(L-lactide-co-ε-caprolactone)), preparing a base film with a polymer in which a chain extender, AFD (Bis(4-aminophenyl)disulfide molecule), is attached to both ends of IPDI, and forming an electrode pattern with the conductive solution.

[0122] Afterwards, the specimen (SH-PLCL) according to the embodiment of the present invention and the specimen (PLCL) according to the comparative example were immersed in a phosphate buffered saline solution (PBS, Phosphate Buffered Saline) with a pH of 7 and subjected to ultrasonic treatment.

[0123] (a) As shown, the specimen (PLCL) according to the comparative example showed that the electrode pattern was damaged and peeled off by ultrasonic treatment for 5 minutes, whereas the specimen (SH-PLCL) according to the embodiment of the present invention showed that the electrode pattern was maintained without damage even after ultrasonic treatment for 1 hour.

[0124] (b) As shown, the specimen according to the embodiment of the present invention (SH-PLCL) and the specimen according to the comparative example (PLCL) were found to have almost identical impedances before and after ultrasonic treatment in the phosphate buffered saline solution. In the case of the specimen according to the comparative example (PLCL), high impedance was maintained with changes in frequency when ultrasonically treated for 5 minutes in the phosphate buffered saline solution, whereas in the case of the specimen according to the embodiment of the present invention (SH-PLCL), the impedance before and after ultrasonic treatment for 1 hour in the phosphate buffered saline solution was found to remain almost identical regardless of changes in frequency.

[0125] Referring to (c), the specimen (SH-PLCL) according to the embodiment of the present invention and the specimen (PLCL) according to the comparative example were 1.7 mA / cm² before phosphate buffered saline solution and ultrasonic treatment. 2 It was found to have the same charge storage capacity. In the case of the specimen according to the comparative example (PLCL), it was found that the charge storage capacity decreased significantly when sonicated in a phosphate buffered saline solution for 5 minutes.

[0126] On the other hand, in the case of the specimen (SH-PLCL) according to the embodiment of the present invention, it is confirmed that there is almost no change before and after sonication in a phosphate buffered saline solution for 1 hour.

[0127] As such, the electronic device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention is applicable in humid environments and physiological conditions (pH 7, 37℃) and can stably detect electrical changes.

[0129] FIG. 16 is a drawing showing an electric device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention. FIG. 16 (a) is an enlarged image of an electric device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention, FIG. 16 (b) shows the change in electrical performance of a temperature sensor after self-healing of an electric device (10) using a self-healing biodegradable elastic conductor, FIG. 16 (c) shows the change in capacitance of a humidity sensor after self-healing of an electric device (10) using a self-healing biodegradable elastic conductor, and FIG. 16 (d) shows the change in electrical performance of a pressure sensor after self-healing of an electric device (10) using a self-healing biodegradable elastic conductor.

[0130] In an embodiment of the present invention, an electronic device (10) using a self-healing biodegradable elastic conductor had its temperature sensor, humidity sensor, and pressure sensor cut using a razor blade to measure the change in performance after self-healing, and the change after self-healing was observed.

[0131] Referring to FIG. 16, an electronic device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention was shown to maintain the sensitivity of temperature, humidity, and pressure sensors almost the same before physical damage and after physical damage was self-healed.

[0133] FIG. 17 is a drawing showing an electric device (10) using a self-healing biodegradable elastic conductor according to an embodiment of the present invention applied in a living body.

[0134] Referring to FIG. 17, an electric device using a self-healing biodegradable elastic conductor according to an embodiment of the present invention can be implanted in a bladder in vivo to monitor the physiological function of the bladder. The electric device (10) using a self-healing biodegradable elastic conductor is made of a soft and flexible material and can be installed in the bladder without sutures to monitor the physiological function of the bladder.

[0136] FIG. 18 is a graph showing the results of functional recovery for artificial damage to an electric device while monitoring the urination behavior of the bladder in real time through an electric device (10) using a self-healing biodegradable elastic conductor of FIG. 17. FIG. 18 (a) shows changes in intravesical pressure, strain, and electromyography (EMG) for damage to the electric device (10) using a self-healing biodegradable elastic conductor, and FIG. 18 (b) shows the damage and recovery process of the strain sensor and electromyography sensor when damage occurs to the electric device (10) using a self-healing biodegradable elastic conductor.

[0137] Referring to FIG. 18, when an electric device (10) using a self-healing biodegradable elastic conductor implanted in the bladder periodically monitors the urination process through deformation and electromyography signals, if the deformation sensor or electromyography sensor is intentionally damaged, the signal from the deformation sensor or electromyography sensor is immediately interrupted due to the damage, but is quickly restored within 5 seconds.

[0139] Although the present invention has been described in detail using preferred embodiments, the scope of the invention is not limited to specific embodiments and should be interpreted by the appended claims. Furthermore, those skilled in the art will understand that many modifications and variations are possible without departing from the scope of the invention. Explanation of the symbols

[0141] 10: Electronic device using a self-healing biodegradable elastomer 100: 1st base film 200: First electrode pattern 300: Second Base Film 400: Second electrode pattern S10: First base film preparation step S20: First electrode pattern formation step S30: 1st annealing step S40: Second base film preparation step S50: Second electrode pattern formation step S60: Second annealing step S70: 3rd annealing stage

Claims

Claim 1 The method comprises the steps of: forming a first electrode pattern on one side of a first base film and annealing the first base film having the first electrode pattern formed thereon at a temperature range of 130°C to 150°C; forming a second electrode pattern on one side of a second base film and annealing the second base film having the second electrode pattern formed thereon at the temperature range; and annealing by applying pressure at a temperature lower than the temperature range while the second base film having the second electrode pattern formed thereon is placed on the upper surface of the first base film having the first electrode pattern formed thereon, wherein the first base film and the second base film are each made of a polymer in which a diisocyanate is bonded to both ends of a biodegradable polymer and a chain extender having a disulfide bond structure is bonded to the ends of the diisocyanate, and the first electrode pattern and the second electrode pattern are each provided as a mixed solution of a conductive polymer, an ionic liquid, polyethylene glycol, and glycerol. Method of manufacturing an electronic device. Claim 2 A method for manufacturing an electronic device according to claim 1, wherein the biodegradable polymer is PLCL (poly(L-lactide-co-ε-caprolactone)), the diisocyanate is IPDI (isophorone diisocyanate (IPDI)), and the chain extender is AFD (Bis(4-aminophenyl)disulfide molecule). Claim 3 A method for manufacturing an electronic device according to claim 2, wherein the conductive polymer is selected from at least one of PEDOT:PSS, polypyrrole (PPy), and polyaniline (PANI), and the ionic liquid is P14[TFSI](N-methyl-N-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide). Claim 4 A method for manufacturing an electronic device according to claim 1, wherein the conductive polymer, the ionic liquid, the polyethylene glycol, and the glycerol are mixed in a ratio of 1:2:4:

5. Claim 5 delete Claim 6 A method for manufacturing an electronic device according to claim 1, wherein the base film has a thickness of 10 to 500 μm and the electrode pattern has a thickness of 0.1 μm to 5 μm. Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete

Citation Information

Patent Citations

  • Polymer composition, conducting film with improved water resistance and durability, and method for preparing the same

    KR101796548B1

  • Self-repair composite material and sensing platform unit

    US20240043641A1

  • Disulfide-containing self-healing polymer blend

    WO2018108950A1

  • Biodegradable solid electrolyte and preparing method of the same

    KR102325518B1